Livestock in irrigated farming systems of Uttar Pradesh - SINGH, S P; GILL, M S; GANGWAR, B; SINGH, M P (The Indian Journal of Animal Sciences, 2011)
The study was taken up to work out an economic potential of livestock in irrigated farming systems of western Uttar Pradesh. The study based on 197 farmers of different size groups i.e. 63 marginal (<1 ha), 66 small (>1 to 2), 44 medium (>2 to 4 ha) and 25 large (>4 ha) randomly selected from 4 blocks of Bagpat and Ghaziabad district of Uttar Pradesh. On the whole the farmers in comparison to 1.82 buffalo out of 4.35 total animals kept, these were 0.58 crossbred cows clearly showed that crossbred breeding programme needs a special attention in the area. Most of the credit was disbursed toward crop cultivation. The employment from livestock activities was inversely related to farm size. Livestock constitutes about 39% of total income of marginal farmers while its share was only about 8% for large farmers. It indicated that the dairy business has wide scope on all farm size categories. Elasticity of coefficients in general varied from 0.096 for fertilizer consumption to 0.282 for area under other crops i.e. cereals, pulses, oilseeds and fodder etc. Elasticity coefficients for dairy animals were significantly positive for all size of farms indicating very good scope of livestock for increasing farm income. Fragmentation and subdivision of land holding, scarcities of labour, low yield of local seeds, less reliable market in context of changing global market, scarcity of owned fund exogenous factors like, dependence of natural resources, global warming, non availability of good quality seeds (variety and breeds) and shades for animals, poultry etc. were major constraints in following integrated farming system. Farmers were agreeing that integrated farming system maintain suitable production system without damaging resource base/environment. It provides family employment throughout the year. It enables recycling the waste with in farming system and provides balance food ultimately a goodapproach for improving standards of living by increasing resource use efficiency and income generation round the year. Farmers may be encouraged for commercializing dairy activity by providing credit, marketing and high productive dairy animals.